Real-World Effectiveness of Adjuvant Oxaliplatin Chemotherapy in Stage III Colon Cancer: A Controlled Interrupted Time Series Analysis - Huang, Wen-Kuan; Hsu, Hung-Chih; Chang, Shu-Hao; Chou, Wen-Chi; Chang, Pei-Hung; Chiang, Sum-Fu; Chang, John Wen-Cheng; Chen, Jen-Shi; Yang, Tsai-Sheng; See, Lai-Chu (Frontiers in Pharmacology, 2021)
Background: The real-world effectiveness of oxaliplatin in stage III colon cancer has not been determined in a large-scale population. We aimed to assess the real-world impact of adjuvant oxaliplatin treatment on the survival of these patients. Methods: Based on Taiwan cancer registry, we evaluated 17,801 patients with resected stage III colon cancer, including 14,168 patients receiving adjuvant chemotherapy and 3,633 not receiving adjuvant chemotherapy as the control group between 2004 and 2014. We used the controlled interrupted time-series analysis to assess the three-year disease-free survival and five-year overall survival rates before (2004-2008) and after (2009-2014) the addition of oxaliplatin. Results: The introduction of oxaliplatin was associated with no significant improvement in the slopes (per half-year) of the three-year disease-free survival rate (0.2%, 95% confidence interval: -1.7%–2.2%) and five-year overall survival rate (0.6%, 95% confidence interval: -1.8%–3%). The patients receiving oxaliplatin-based chemotherapy also showed no significant increase in the slopes (per half-year) of the three-year disease-free survival rate (0.6%, 95% confidence interval: -1.4%–2.6%) and five-year overall survival rate (1%, 95% confidence interval: -1.5%–3.5%). The nonsignificant results were consistent across subgroup analyses of age (<70 years vs ≥70 years), recurrence risk (T1-3 or N1 vs T4 or N2), and cycle of oxaliplatin use (≤6 vs >6 ). However, oxaliplatin-based chemotherapy significantly increased the slope (per half-year) of the five-year OS (2%, 95% confidence interval: 0.2%–3.8%) for patients in the high-risk group (T4 or N2). The present results were robust in several sensitivity analyses. Conclusion: Among real-world patients with stage III colon cancer, the introduction of oxaliplatin does not yield a significant improvement in survival. Future work should identify the subpopulation(s) of patients who benefit significantly from the addition of oxaliplatin.